Study of the effect of synthesis parameters in the electrical conductivity of the composite poly (vinylidene fluoride) / polyaniline - Duarte,Glaucea Warmeling (2017)
ABSTRACT The electroactive polymers have been the subject of many studies in the last decade, mainly because its unique properties. They are used in composite structures, which allow its application in many fields, as for example, sensors and artificial muscles. The electrical properties of these composites are influenced by the doping state of the electroactive polymer, which is controlled during its synthesis process. Therefore, this work aimed to evaluate how the synthesis parameters influence the electrical conductivity of the composite PANI/PVDF. The synthesis parameters evaluated were the concentrations of monomer, initiator and dopant, and the synthesis time. PANI was obtained by chemical polymerization in a solution containing PVDF and the solvent DMF. To evaluate possible changes in the chemical structure of the composite, the samples were submitted to FT-IR and XRD analysis. It was possible to conclude that the parameters relative to the production of PANI directly influence in the electrical conductivity of the composite. So, the sample produced with major quantities of monomer, initiator and dopant were statistically significant to increase the electrical property of the composite.